Using Visual Scene Displays as Communication Support Options for People with Chronic, Severe Aphasia: A Summary of AAC Research and Future Research Directions. (3rd July 2015) - Beukelman, David R.; Hux, Karen; Dietz, Aimee; McKelvey, Miechelle; Weissling, Kristy
Abstract: Research about the effectiveness of communicative supports and advances in photographic technology has prompted changes in the way speech-language pathologists design and implement interventions for people with aphasia. The purpose of this paper is to describe the use of photographic images as a basis for developing communication supports for people with chronic aphasia secondary to sudden-onset events due to cerebrovascular accidents (strokes). Topics include the evolution of AAC-based supports as they relate to people with aphasia, the development and key features of visual scene displays (VSDs), and future directions concerning the incorporation of photographs into communication supports for people with chronic and severe aphasia.